An overview of solvent extraction processes developed in Europe for advanced nuclear fuel recycling, part 1 — heterogeneous recycling. Issue 11 (24th July 2021) - Geist, Andreas; Adnet, Jean-Marc; Bourg, Stéphane; Ekberg, Christian; Galán, Hitos; Guilbaud, Philippe; Miguirditchian, Manuel; Modolo, Giuseppe; Rhodes, Chris; Taylor, Robin
ABSTRACT: The hydrometallurgical separation concepts for the heterogeneous recycling of irradiated nuclear fuel developed in Europe are presented and discussed. Most of these concepts were developed within European collaborative projects and involve solvent extraction processes separating trivalent minor actinides (with a focus on americium) from the raffinate solution from processes such as PUREX (Plutonium Uranium Reduction Extraction) or an evolution of PUREX. Depending on the process chemistry applied, process schemes each consisting of one, two or three solvent extraction cycles are required to obtain a pure americium product. The various solvent extraction processes are briefly introduced. The most suitable choices are selected, and the process schemes are compared to one another.